2009
DOI: 10.1213/ane.0b013e3181ae0989
|View full text |Cite
|
Sign up to set email alerts
|

An Anatomical Study of the Transversus Abdominis Plane Block: Location of the Lumbar Triangle of Petit and Adjacent Nerves

Abstract: The lumbar triangles of Petit found in the specimens in this study were more posterior than the literature suggests. The position of the lumbar triangle of Petit varies largely and the size is relatively small. The relevant nerves to be blocked had not entered the TAP in the specimens in this study at the point of the lumbar triangle of Petit. At the midaxillary line, however, all the nerves were in the TAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 9 publications
1
72
0
12
Order By: Relevance
“…1 Jankovic et al have demonstrated the exact location of nerves needed to be blocked in petite triangle (inferior lumbar triangle) to get good block. 9 The current study was lacking a few aspects like we did not determine the duration of the TAP block and the exact volume needed on body weight basis. Also, we did not assess postoperative nausea and vomiting in the PACU.…”
Section: Discussionmentioning
confidence: 96%
“…1 Jankovic et al have demonstrated the exact location of nerves needed to be blocked in petite triangle (inferior lumbar triangle) to get good block. 9 The current study was lacking a few aspects like we did not determine the duration of the TAP block and the exact volume needed on body weight basis. Also, we did not assess postoperative nausea and vomiting in the PACU.…”
Section: Discussionmentioning
confidence: 96%
“…It supplies the upper and medial part of the thigh and part of the skin covering the genitalia. (3) The transverus abdominis plane thus provides a space in to which local anesthetic can be deposited to achieve myocutaneous sensory blockade 17,25 The dose of the drug used was bupivacaine 0.25% 20ml on each side, maximum dose being 2mg/k.g. higher recommended dose of bupivacaine was used to provide prolonged analgesia with single shot technique.…”
Section: Discussionmentioning
confidence: 99%
“…However, the triangle is highly variable in site and presence. 19,47,48 Consequently, the ultrasonography guided technique was described. 49 Other technical variants include a 'multiple injection' Figure 6 Mean length of hospital stay technique and continuous infusion via a subcutaneous catheter.…”
Section: Addition Of Transversus Abdominis Plane Block To Patient Conmentioning
confidence: 99%